Timber robotic fabrication: testing for an integral manufacturing - El Khoury, Chadi; Halabi, Marwan (International Journal of Engineering and Technology, 2018)
Going beyond sustainability and with the great development of technology, timber has a great potential to be explored as a building material. Its physical-mechanical properties such as lightness and elasticity allow the designing of complex structures and the growing trend in research in robotic fabrication has accelerated the development of dimensional design concepts that demonstrate that wood is absolutely contemporary and at the height of other innovative materials. This paper investigates on computer aided integrated architectural design and production of timber using advanced automated tools, aiming to provide integral solutions for the design and production of geometrically complex free-form architecture. Investigations on computer aided geometric design and integrated manufacturing are carried out with equal importance. This research is considering an integral and interdisciplinary approach, including computer science, robotics and architecture. The studies for translation of the geometrical into constructional elements consider integrated manufacturing. Addressing and numbering of the elements by iterative geometric design are investigated and compared to lexicographically ordered addressing systems, in order to provide an adequate data structure for the design, production and assembly of the constructional elements. The integrated digital design methods studied are tested and verified by the realization of one to one scale prototypes. The main aim of the research is to find ways of shifting the perspective of adventurous high quality architecture robotically produced with correspondingly reduced costs and minimized environmental impact.